MiR-154-5p-MCP1 Axis Regulates Allergic Inflammation by Mediating Cellular Interactions - Kim, Misun; Jo, Hyein; Kwon, Yoojung; Jeong, Myeong Seon; Jung, Hyun Suk; Kim, Youngmi; Jeoung, Dooil (Frontiers in Immunology, 2021)
In a previous study, we have demonstrated that p62, a selective receptor of autophagy, can regulate allergic inflammation. In the present study, microRNA array analysis showed that miR-154-5p was increased by antigen (DNP-HSA) in a p62-dependent manner in rat basophilic leukemia cells (RBL2H3). NF-kB directly increased the expression of miR-154-5p. miR-154-5p mediated in vivo allergic reactions, including passive cutaneous anaphylaxis and passive systemic anaphylaxis. Cytokine array analysis showed that antigen stimulation increased the expression of MCP1 in RBL2H3 cells in an miR-154-5p-dependent manner. Reactive oxygen species (ROS)-ERK-NF-kB signaling increased the expression of MCP1 in antigen-stimulated RBL2H3 cells. Recombinant MCP1 protein induced molecular features of allergic reactions both in vitro and in vivo. Anaphylaxis-promoted tumorigenic potential has been known to be accompanied by cellular interactions involving mast cells, and macrophages, and cancer cells . Our experiments employing culture medium, co-cultures, and recombinant MCP1 protein showed that miR-154 and MCP1 mediated these cellular interactions. MiR-154-5p and MCP1 were found to be present in exosomes of RBL2H3 cells. Exosomes from PSA-activated BALB/C mouse induced molecular features of passive cutaneous anaphylaxis in an miR-154-5p-dependent manner. Exosomes from antigen-stimulated RBL2H3 cells enhanced both tumorigenic and metastatic potentials of B16F1 melanoma cells in an miR-154-5p-dependent manner. Exosomes regulated both ROS level and ROS mediated cellular interactions during allergic inflammation. Our results indicate that the miR-154-5p-MCP1 axis might serve as a valuable target for the development of anti-allergy therapeutics.